2021
DOI: 10.2147/iprp.s298660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmaceuticals Inventory Management in Selected Health Facilities of West Arsi Zone, Oromia, Ethiopia

Abstract: Background: Effective inventory management ensures an uninterrupted supply of safe, effective, and affordable pharmaceuticals which could be achieved through developing ABC-VEN (Always, Better, Control-Vital, Essential, Desirable) and FSN-XYZ (Fast, Slow, Nonmoving-High, Medium, Low Value) matrix analysis. ABC-VEN matrix analysis is used to control inventory according to their annual consumption and on their functional importance whereas, FSN-XYZ matrix analysis is applied to control inventory by identifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…In comparison to other studies conducted in Baghdad, India, and Ethiopia, the proportion of vital items and ASV was very high. 14 , 21 , 29 According to the findings, V–items amounted to 18.1%, 19.49%, and 35.1% of total item expenditure in their studies. The difference could be that the agency manages a compiled list of medications from customers with varied levels and preferences.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In comparison to other studies conducted in Baghdad, India, and Ethiopia, the proportion of vital items and ASV was very high. 14 , 21 , 29 According to the findings, V–items amounted to 18.1%, 19.49%, and 35.1% of total item expenditure in their studies. The difference could be that the agency manages a compiled list of medications from customers with varied levels and preferences.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings are consistent with previous studies conducted in India, Turkey, and Ethiopia, which found that class A-items contributed to 72.9%, 80%, and 80.1% of annual drug expenditures, respectively. 17 , 29 , 30 This analysis would enable managers to focus more on class A-items with tight control and no inventory discrepancy, while class C-items would have very little control. As a result, the analysis can assist logistics managers in developing inventory count policies (class A-items can be counted once every week, B-items biweekly, and C-items monthly), and stocking levels (arrange more frequent purchases or delivery of smaller quantities of class A-items).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted in Kenya revealed that there was a huge mismatch between the criticality of the product (VEN) and expenditure-based classification (ABC) of pharmaceutical items [ 19 ]. FSN–XYZ matrix analysis done in Ethiopia showed that an unexpected amount of budget (20%) was disbursed on high-cost and non-moving pharmaceutical items [ 20 ]. Moreover, the study conducted in northern Ethiopia showed that a significant amount of the annual budget (75.86%) was spent on very few pharmaceutical products (17%), which needs management review and engagement in the whole process of the hospital's supply chain decisions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them addressed ABC-VEN alone in the same types of health institutions, e.g., [ 7 , 21 23 ]. The others studied at a supplier agency [ 11 ] or in a single zone [ 20 ]. Yet all of them lacked triangulation with qualitative data to provide a deep and complete understanding of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%